2023
DOI: 10.1192/bjo.2023.526
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with suicidal ideation among students taking university entrance tests: revisited and a study based on Geographic Information System data

Abstract: Background A previous study identified students taking Bangladeshi university entrance tests as a vulnerable group at a higher risk of suicidal behaviours before the COVID-19 pandemic. However, the impact of the pandemic on the magnitude of these behaviours among this population remains unexplored. Aims This study aimed to investigate the prevalence of suicidal ideation and associated factors among Bangladeshi university entrance test takers following the pandemic. In addition, an approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Previous studies reported that students who failed in first-time university entrance tests had a higher rate of mental health problems. For instance, studies conducted among similar students taking university entrance tests reported that repeat test takers had higher rates of depression, anxiety, burnout, and suicidal behaviors, as found in the studies conducted before the pandemic [ 15 ], and during the pandemic [ 17 ]. It is also reported that mental health problems had significant associations with different types of digital addiction, for instance, smartphone addiction [ 7 , 30 , 31 ], Facebook addiction [ 22 ], nomophobia [ 29 ], internet addiction [ 6 ], and social media addiction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that students who failed in first-time university entrance tests had a higher rate of mental health problems. For instance, studies conducted among similar students taking university entrance tests reported that repeat test takers had higher rates of depression, anxiety, burnout, and suicidal behaviors, as found in the studies conducted before the pandemic [ 15 ], and during the pandemic [ 17 ]. It is also reported that mental health problems had significant associations with different types of digital addiction, for instance, smartphone addiction [ 7 , 30 , 31 ], Facebook addiction [ 22 ], nomophobia [ 29 ], internet addiction [ 6 ], and social media addiction [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic information, including variables such as gender, permanent residence (rural and urban), religion, family type, and monthly family income. Participant’s family was categorized into three distinct groups: those with incomes less than 15,000 Bangladeshi Taka (BDT), those falling within the 15,000–30,000 BDT range, and those with monthly family incomes exceeding 30,000 BDT as following the previous study within the similar population [ 17 ]. For religion, others represent those studies belonging to a religion other than Muslim, that is, Hindu, Christianity, Buddhism, etc.…”
Section: Methodsmentioning
confidence: 99%